(untitled) (Uzbek Scholar Journal, 2023)
The new content of language education is focused on mastering several foreign languages by graduates of higher educational institutions. The process of studying at the higher school is aimed at training a competent, responsible specialist, fluent in the profession, capable of functional use of a foreign language in various fields of activity and intercultural communication.